Analysis of strain difference in behavior to Cholecystokinin (CCK) receptor mediated drugs in PVG hooded and Sprague-Dawley rats using elevated plus-maze test apparatus - Farook, J.M. (2012)
10.1016/j.neulet.2004.01.027